Potential Impact of Metabolic and Gut Microbial Response to Pregnancy and Lactation in Lean and Diet‐Induced Obese Rats on Offspring Obesity Risk. Issue 4 (22nd January 2018) - Paul, Heather A.; Collins, Kelsey H.; Bomhof, Marc R.; Vogel, Hans J.; Reimer, Raylene A.
Abstract : Scope: Maternal obesity programs metabolic dysfunction in offspring, increasing their susceptibility to obesity and metabolic diseases in later life. Moreover, pregnancy and lactation are associated with many metabolic adaptations, yet it is unclear how diet‐induced maternal obesity may interrupt these processes. Methods and results: 1 H NMR serum metabolomics analysis was performed on samples collected pre‐pregnancy and in pregnant and lactating lean and high fat/sucrose (HFS) diet‐induced obese Sprague‐Dawley rats to identify maternal metabolic pathways associated with developmental programming of offspring obesity. Gut microbial composition was assessed using qPCR. Offspring of HFS dams had nearly 40% higher adiposity at weaning compared to offspring of lean dams. While pregnancy and lactation were associated with distinct maternal metabolic changes common to both lean and obese dams, we identified several metabolic differences, potentially implicating dysregulated one‐carbon and mammary gland metabolism in the metabolic programming of obesity. Gut microbial composition was significantly altered with obesity, and both gestation and lactation were accompanied by changes in gut microbiota. Conclusion: Diet‐induced maternal obesity and consumption of an obesogenic maternal diet results in differential metabolic and gut microbial adaptations to pregnancy and lactation; these maladaptations may be directly involved in maternal programming of offspring susceptibility to obesity. Abstract : 1 H NMR serum metabolomics analysis and gut microbial profiling in lean and high fat/sucrose diet‐induced obese rats across pre‐pregnancy, gestation, and lactation is carried out, with the goal of identifying metabolic pathways involved in the developmental programming of offspring obesity. Differences between maternal groups in one‐carbon and branched chain amino acid metabolism are identified, as well as gut microbiota composition, while also highlighting pathways likely involved in key metabolic adaptations to pregnancy and lactation.